Students' Grammatical Errors in Essay Writing: A Pedagogical Grammar Reflection - Fitrawati, Fitrawati; Safitri, Dian (International Journal of Language Education, 2021)
Students of English as a Foreign Language (EFL) are expected to master the fundamental of grammar so they can produce good essays. However, despite having learnt English at secondary or university level, students tend to make many grammatical errors in their writing. This study presents the grammatical errors made by college EFL students in their essays and the pedagogical implications viewed from those errors. This is a descriptive research with 30 second-year students who enrolled Essay Writing class as participants. Thirty written essays produced by the students were analyzed for the grammatical errors. The findings revealed that there were 368 grammatical errors found in the students’ essays. The most common one was in verb use (48%). Besides, the errors were also found in nouns (12%), prepositions (8%), determiners (8%), pronouns (8%), adverbials (6), adjectives (5%), and conjunctions (5%). If teachers do not assist students to comprehend the concept of parts of speech, and essential and nonessential clauses, these students will continue to make errors in their more advanced writing. The findings may have useful pedagogical implications for English language teachers, syllabus designers, and test developers. Understanding students’ difficulties and providing appropriate grammar instructions are the keys to teach grammar.